Who is afraid of obstetric violence? - Leila Katz; Melania Maria Amorim; Juliana Camargo Giordano; Maria Helena Bastos; Aline Veras Morais Brilhante
Abstract Despite being a relatively new term, obstetric violence is an old problem. In 2014, the World Health Organization declared: "Many women experience disrespectful and abusive treatment during childbirth in facilities worldwide. Such treatment not only violates the rights of women to respectful care, but can also threaten their rights to life, health, bodily integrity, and freedom from discrimination". This problem, named as "abuse", "disrespect" and/or "mistreatment" during childbirth, has been addressed in several studies. However, there has been no consensus on how to properly name this problem, although its typology has been well described. Considering the magnitude of this problem, it is essential to give the correct terminology to this important health and human rights issue. Naming it as obstetric violence and understanding it as gender-based violence will ensure appropriate interventions to avert this violation of women's rights.